2010
DOI: 10.1172/jci40027
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response protects human tumor cells during hypoxia through regulation of the autophagy genes MAP1LC3B and ATG5

Abstract: Tumor hypoxia is a common microenvironmental factor that adversely influences tumor phenotype and treatment response. Cellular adaptation to hypoxia occurs through multiple mechanisms, including activation of the unfolded protein response (UPR). Recent reports have indicated that hypoxia activates a lysosomal degradation pathway known as autophagy, and here we show that the UPR enhances the capacity of hypoxic tumor cells to carry out autophagy, and that this promotes their survival. In several human cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
636
3
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 720 publications
(675 citation statements)
references
References 75 publications
32
636
3
4
Order By: Relevance
“…[33][34][35][36][37] In this regard, recent studies have identified DDIT3 as a direct regulator of numerous genes involved in the autophagic process. [38][39][40] Here, we show that the increase of transcripts levels of several autophagy-and lysosome-related genes in colchicinetreated fish paralleled that of Ddit3 mRNA supporting these previous studies. However, the increase of lysosomal transcripts was not followed by an increase of the lysosomal function (as evidenced by the activity of CTSD), in line with the demonstrated inhibition of the autophagic flux in our samples and the recently published data showing that activation of lysosomal function depends on autophagosome-lysosome fusion.…”
Section: Discussionsupporting
confidence: 89%
“…[33][34][35][36][37] In this regard, recent studies have identified DDIT3 as a direct regulator of numerous genes involved in the autophagic process. [38][39][40] Here, we show that the increase of transcripts levels of several autophagy-and lysosome-related genes in colchicinetreated fish paralleled that of Ddit3 mRNA supporting these previous studies. However, the increase of lysosomal transcripts was not followed by an increase of the lysosomal function (as evidenced by the activity of CTSD), in line with the demonstrated inhibition of the autophagic flux in our samples and the recently published data showing that activation of lysosomal function depends on autophagosome-lysosome fusion.…”
Section: Discussionsupporting
confidence: 89%
“…In polyQ72-loaded mammalian cells, the phosphorylation of eIF2α up-regulates the expression of Atg12 [157]. During the unfolded protein response, triggered by hypoxia, the transcription factors ATF4 and CHOP, which are regulated by PERK, increase the expression of Map1lc3b and Atg5, respectively [158]. Glyceraldehyde-3-phosphate dehydrogenase, a multifunctional enzyme known to play a role in glycolysis as well as having other less well-understood roles such as transcriptional coactivation, has also been shown to upregulate the transcription of Atg12 to protect cells against caspase-independent cell death [159].…”
Section: Nf-κbmentioning
confidence: 99%
“…In some scenarios, the induction of autophagy is accompanied by increased mRNA levels of certain autophagy genes such as LC3B, ATG5 or ATG12. 5 However, little is known about the mechanisms that controls ATG protein translation. Indeed, there are opposite opinions about the need of protein translation in starvation-induced autophagy.…”
Section: Introductionmentioning
confidence: 99%